2021
DOI: 10.3389/fmicb.2021.684340
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Protein Levels on Dynamic Changes and Interactions of Ruminal Microbiota and Metabolites in Yaks on the Qinghai-Tibetan Plateau

Abstract: To improve performance and optimize rumen function in yaks (Bos grunniens), further knowledge on the appropriate dietary protein levels for ruminal microbiota and the metabolite profiles of yaks in feedlot feeding is necessary. Current understanding of dietary protein requirements, ruminal microbiota, and metabolites is limited. In this study, yaks were fed a low-protein diet (L; 9.64%), middle low-protein diet (ML; 11.25%), middle high-protein diet (MH; 12.48%), or a high-protein diet (H; 13.87%), and the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 65 publications
4
11
0
Order By: Relevance
“…Additionally, an association was found between the structure of the rumen microbiota and metabolic profiles. These results were consistent with those in donkeys ( 64 ), yaks ( 65 ), Holstein heifers ( 18 ), mice ( 66 ) and humans ( 67 ), revealing a close relationship between microbiota, metabolites and organismal health. Our study also found significant positive correlations between the dominant bacterial groups and differential metabolites using Spearman correlation analysis.…”
Section: Discussionsupporting
confidence: 87%
“…Additionally, an association was found between the structure of the rumen microbiota and metabolic profiles. These results were consistent with those in donkeys ( 64 ), yaks ( 65 ), Holstein heifers ( 18 ), mice ( 66 ) and humans ( 67 ), revealing a close relationship between microbiota, metabolites and organismal health. Our study also found significant positive correlations between the dominant bacterial groups and differential metabolites using Spearman correlation analysis.…”
Section: Discussionsupporting
confidence: 87%
“…In our study, trend lines between the groups revealed that organic acids and their associated metabolites are the most significantly affected metabolites detected in the fecal samples. Our results are in line with the previous study [ 23 ] as they also documented organic acids’ most altering metabolites in the rumen samples of the yaks fed different dietary protein levels. The possible reason might be more protein availability for degradation, which results in greater amino-acid availability in the small intestine for microbial downstream to supply the end products for liver metabolism.…”
Section: Discussionsupporting
confidence: 93%
“…(4) Rikenellaceae_RC9_gut_group also belongs to the same phylum, and its members are producers of shortchain fatty acids. The higher abundance of the Rikenellaceae_RC9_gut_group ensures a high proportion of propionic acid in the rumen and thus regulates the balance in the intestine [32]. (5) norank_f__norank_o__Clostridia_UCG-014 is tolerant to gastric acid, enters the intestine, inhibits the growth of harmful intestinal bacteria, restores the function of intestinal ora, improves immunity and promotes the absorption, digestion and assimilation of nutrients [33].…”
Section: Effect Of Glr On the Structural Diversity Of Broiler Manure ...mentioning
confidence: 99%